2024
DOI: 10.1007/s10637-023-01410-2
|View full text |Cite|
|
Sign up to set email alerts
|

CXCR2 antagonist navarixin in combination with pembrolizumab in select advanced solid tumors: a phase 2 randomized trial

Andrew J. Armstrong,
Ravit Geva,
Hyun Cheol Chung
et al.

Abstract: SummaryC-X-C motif chemokine receptor 2 (CXCR2) has a role in tumor progression, lineage plasticity, and reduction of immune checkpoint inhibitor efficacy. Preclinical evidence suggests potential benefit of CXCR2 inhibition in multiple solid tumors. In this phase 2 study (NCT03473925), adults with previously treated advanced or metastatic castration-resistant prostate cancer (CRPC), microsatellite-stable colorectal cancer (MSS CRC), or non–small-cell lung cancer (NSCLC) were randomized 1:1 to the CXCR2 antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Another avenue with the potential to aid in cancer treatment is the control and trafficking of immune cells to cancer, including MDSCs and Tregs, summarized in this review. Preclinical and clinical attempts to suppress cancer by antagonizing CCR2, CCR4, CCR5, CXCL8, CXCR1/2, CXCR4 combined with or without other therapies [206,222,229,[466][467][468][469][470][471][472][473][474][475][476][477] (clinical trials reported by ClinicalTrials.gov: NCT03177187, NCT03851237), by chemokine modulation regimen via cytokine and TLR agonist/antagonist injection [229] (clinical trials reported by ClinicalTrials.gov: NCT06149481, NCT05570825, NCT03161431), or by targeting non-chemokine/chemokine receptor mechanisms such as eATP metabolism [359,362] (clinical trials reported by ClinicalTrials.gov: NCT05234853, NCT05177770, NCT05431270) or complement [304,478] (clinical trials reported by ClinicalTrials.gov: NCT02257528) are being continued.…”
Section: Discussionmentioning
confidence: 99%
“…Another avenue with the potential to aid in cancer treatment is the control and trafficking of immune cells to cancer, including MDSCs and Tregs, summarized in this review. Preclinical and clinical attempts to suppress cancer by antagonizing CCR2, CCR4, CCR5, CXCL8, CXCR1/2, CXCR4 combined with or without other therapies [206,222,229,[466][467][468][469][470][471][472][473][474][475][476][477] (clinical trials reported by ClinicalTrials.gov: NCT03177187, NCT03851237), by chemokine modulation regimen via cytokine and TLR agonist/antagonist injection [229] (clinical trials reported by ClinicalTrials.gov: NCT06149481, NCT05570825, NCT03161431), or by targeting non-chemokine/chemokine receptor mechanisms such as eATP metabolism [359,362] (clinical trials reported by ClinicalTrials.gov: NCT05234853, NCT05177770, NCT05431270) or complement [304,478] (clinical trials reported by ClinicalTrials.gov: NCT02257528) are being continued.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter, randomized, double-blind, placebo-controlled trial on newly diagnosed type 1 diabetes revealed that short-term ladarixin treatment did not significantly preserve residual β-cell function ( 30 ). Navarixin is currently mainly used in the treatment of advanced solid tumors, and there are no experiments investigating the relationship between navarixin and metabolic diseases ( 31 ). Clotrimazole is a broad-spectrum antifungal agent that is mainly used to treat fungal infections such as Candida albicans .…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter, randomized, double-blind, placebo-controlled trial on newly diagnosed type 1 diabetes revealed that short-term ladarixin treatment did not significantly preserve residual b-cell function (30). Navarixin is currently mainly used in the treatment of advanced solid tumors, and there are no experiments investigating the relationship between navarixin and metabolic diseases (31). Clotrimazole is a broad-spectrum antifungal agent that is mainly used to treat fungal infections such as Candida albicans.…”
Section: Discussionmentioning
confidence: 99%